Experience capitalization: perspectives, multiple audiences - Santiago, Fábio (Technical Centre for Agricultural and Rural Cooperation, 2019)
Having participants sharing information and interacting with each other during the experience capitalization process enhances the potential for adoption, adaptation and scaling up.